Respostas
respondido por:
1
x - y = 30
x = 30 + y
substituindo x na igualdade
x = 8
-- --
y 3
30 + y = 8
--------- ---
y 3 multiplicando cruzado
8y = 3(30 + y)
8y = 90 + 3y
8y - 3y = 90
5y = 90
y = 90
---
5
y = 18
x - y = 30
18 - y = 30
- y = 30 - 18
- y = 12 .(-1)
y = - 12
x = 30 + y
substituindo x na igualdade
x = 8
-- --
y 3
30 + y = 8
--------- ---
y 3 multiplicando cruzado
8y = 3(30 + y)
8y = 90 + 3y
8y - 3y = 90
5y = 90
y = 90
---
5
y = 18
x - y = 30
18 - y = 30
- y = 30 - 18
- y = 12 .(-1)
y = - 12
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás